RELIABILITY OF PREDICTION OF GAS SATURATED RESERVOIRS IN BILCHE-VOLYTSYA ZONE USING THE MUDLOGING STATION DATA - VIAZOVSKA, Yevheniia; MYKHALEVYCH, Ihor; KARPYN, Vasyl; DUCHUK, Stepan (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The article analyzed the possibility of prediction reservoir saturation using the Mudlogging station unit. The key factors, which have negative influence on such studies, were analyzed. The inaccuracy of the mudlogging station data could be related to the specific drilling techniques and the use of PDC drilling bits. After all, these data are normally used for the preliminary evaluation of potential reservoir saturation. Then, these data need to be complexed with the result of petrophysical evaluation based on well log results. Taking into account the limited resolution of logging methods in the thin-layered Sarmatian section and in compacted Upper Jurassic carbonates, the decision on the test object is sometimes made based on core data and aforementioned gas readings. This article will discuss whether the mudlogging station data are relevant for solving such problems and how they statistically correlate with the test results. Methods. The analysis of gas anomalies recorded by the mudloging station included several stages: selection of wells for comparison of gas anomalies in which a commercial gas inflow was obtained based on petrophysical evaluation of reservoirs and formation pressure; consideration of the lag time of gas exit from the bottom hole, gas from the swabbing procedures, gas after drilling string build-up, recirculation gas, and places where petroleum product were added into the drilling fluid. Results. A detailed analysis of gas anomalies was performed; petrophysical assessment of the reservoirs in the intervals of increased gas reading was performed; contrast ratio were calculated in perforated intervals in 11 wells. Conclusions. The relevance of Mudlogging station data for preliminary identification of potentially gas-saturated horizons has been confirmed. Contrast ratio (Kkon) is an informative indicator in the analysis of gas anomalies. Kkon values within 4.3–6.3 indicate the possible gas saturated interval.